Development of atlas Kingdom Plantae morphology of mangrove plant based on local potential at PPLH Puntondo Takalar - Akma, Nurul; Hasanah , Ummul; Ibrahim, Misykat Malik (Universitas Islam Negeri Alauddin Makassar, 2023)
Development of atlases needs to be developed through teaching material based on local potential. This study aims to (1) Determine the steps for developing teaching materials atlas kingdom plantae morphology of mangrove plants based on local potential at PPLH Puntondo Takalar; and (2) Test the level of validity, practicality, and effectiveness of teaching materials atlas kingdom plantae morphology of mangrove plants based on potential at PPLH Puntondo Takalar. The ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The development model is used in this type of research and development. Validity, practicality, and effectiveness are evaluated during the product development process. Twenty six (26) students of class XI IPA MA Muhammadiyah Salaka were used as research objects. Product validity is assessed using media validation sheets, practicality the product is assessed using responses from students and educators, and the effectiveness of the product is assessed. The level of data validity is 3.6, meaning it is very valid. The practicality level of the answer is 92%, which means it is very practical. the results of the research, the Magic Box teaching materials should be used because they meet the valid, useful, and effective requirements.